A two-dimensional multi-shelled metal–organic framework and its derived bimetallic N-doped porous carbon for electrocatalytic oxygen reduction. Issue 98 (25th November 2019) - Xu, Yang; Huang, Zhehao; Wang, Bin; Liang, Zuozhong; Zhang, Chaochao; Wang, Yanzhi; Zhang, Wei; Zheng, Haoquan; Cao, Rui
Abstract : We report a multi-shelled two-dimensional metal–organic framework (MOF), which is transferred to a Co/Ni-embedded bimetallic N-doped porous carbon. Abstract : We report a multi-shelled two-dimensional metal–organic framework (MOF), which is transferred to a Co/Ni-embedded bimetallic N-doped porous carbon. The bimetallic N-doped porous carbon exhibits high electrocatalytic activity and long-term stability toward the oxygen-reduction reaction (ORR) and Zn–air batteries.